Disease status in patients with chronic myeloid leukemia is better characterized by BCR-ABL/BCR transcript ratio than by BCR-ABL transcript level, which may suggest a role of normal BCR gene in the disease pathogenesis - Moravcova, J; Regner, J; Mouckova, D; Fiser, K; Zmekova, V; Malacova, R; Michalova, K; Klamova, H (Neoplasma, 2005)
Monitoring of BCR-ABL transcript level is widely used in chronic myeloid leukemia (CML) to follow up response to therapy. In this study we compare abilities of two quantitative RT-PCR assays to characterize the disease status in CML patients: RT-PCR quantifying the BCR-ABL transcript concentration and RT-PCR determining the BCR-ABL/BCR transcript ratio (R). We demonstrate that in non-responders only R, but not BCR-ABL, unambiguously characterizes the state of disease. Moreover, R values >1 found in all poor responders indicate lower BCR expression compared to BCR- ABL in these patients. Our results demonstrate the importance of BCR-ABL/BCR transcript ratio for the disease status and the disease prognosis characterization and suggest a possible role of the normal BCR gene expression in CML pathogenesis.
Keywords: mužské pohlaví; geny abl; Male; senioři; Genes, abl; protoonkogenní proteiny c-bcr; Female; Humans; tyrosinkinasy; Prognosis; lidé; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Middle Aged; progrese nemoci; ženské pohlaví; lidé středního věku; Proto-Oncogene Proteins c-bcr; Longitudinal Studies; Cell Transformation, Neoplastic; Proto-Oncogene Proteins; prognóza; Protein-Tyrosine Kinases; Reverse Transcriptase Polymerase Chain Reaction; nádorová transformace buněk; longitudinální studie; polymerázová řetězová reakce s reverzní transkripcí; dospělí; Disease Progression; Adult; chronická myeloidní leukemie; protoonkogenní proteiny; Aged